Prediction and attribution of quiescent tropical cyclone activity in the early summer of 2016: case study of lingering effects by preceding strong El Niño events. (25th July 2017) - Takaya, Yuhei; Kubo, Yutaro; Maeda, Shuhei; Hirahara, Shoji
Abstract : The ocean modulates seasonal tropical cyclone (TC) activity in the western North Pacific in various ways. This study investigates mechanisms contributing to the quiescent TC activity during the early summer (May–July) of 2016 using an atmosphere– ocean coupled model. Numerical simulations indicate that the Indian Ocean warming induced by the preceding El Niño dominantly contributed to the quiescent TC activity, implying high predictability of seasonal TC activity in the early summer. Abstract: We investigated mechanisms contributing to the quiescent tropical cyclone (TC) activity in the western North Pacific (WNP) during the early summer (May–July) of 2016 by conducting and analysing seasonal predictions and sensitivity experiments with an atmosphere–ocean coupled model. In the seasonal prediction experiment, the model successfully predicted the inactive TC condition. Sensitivity experiment simulations, in which the warmer‐than‐normal sea surface temperature (SST) in the Indian Ocean (IO) was restored to the climatology, represented a weakened lower‐tropospheric anticyclonic anomaly and near‐normal TC activity over the WNP. These results suggest that the quiescent TC activity is attributable to the warm IO SST anomalies induced by the preceding 2015/2016 El Niño. Verification and analysis of reforecasts indicated that the TC count in early summer is highly predictable due to IO warming, a lingering effect of preceding El Niño events.